A study on Occurrence of Sowing Rains for Long, Medium and Short Duration Crop in Bangalore Region - Rao, B V Ramana; Biradar, B R; Surpur, S S (Annals of Arid Zone, 2016)
The occurrence of sowing rains for long, medium and short duration crops at Bangalore was studied by analysing the daily rainfall data recorded at Bangalore for the years 1921 to 1970. It was deserved that it is possible to sow anyone of the three varieties in time during most of the years. It is risky to depend only on one set of seeds and the farmers should be ready with any two sets of seeds of different durations so that they can successfully sow the seeds during the optimum period in about 85 per cent of the years. The information furnished will be useful for adopting a strategy in seed production and distribution and for evolving cropping patterns under dry land conditions.